2011
DOI: 10.1111/j.1365-2141.2010.08499.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Ca2+ modulates ADP‐evoked aggregation through altered agonist degradation: implications for conditions used to study P2Y receptor activation

Abstract: ADP is considered a weak platelet agonist due to the limited aggregation responses it induces in vitro at physiological concentrations of extracellular Ca2+ [(Ca2+)o]. Lowering [Ca2+]o paradoxically enhances ADP-evoked aggregation, an effect that has been attributed to enhanced thromboxane A2 production. This study examined the role of ectonucleotidases in the [Ca2+]o-dependence of platelet activation. Reducing [Ca2+]o from millimolar to micromolar levels converted ADP (10 μmol/l)-evoked platelet aggregation f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 41 publications
(69 reference statements)
3
24
0
Order By: Relevance
“…Addition of ADP to washed platelets results in shape change, reversible aggregation at physiological concentrations of calcium (2 mM) and finally desensitization [10,11]. Transduction of the ADP signal involves a transient rise in free cytoplasmic calcium, due to mobilization of internal stores, secondary store-mediated influx and a concomitant inhibition of adenylyl cyclase activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Addition of ADP to washed platelets results in shape change, reversible aggregation at physiological concentrations of calcium (2 mM) and finally desensitization [10,11]. Transduction of the ADP signal involves a transient rise in free cytoplasmic calcium, due to mobilization of internal stores, secondary store-mediated influx and a concomitant inhibition of adenylyl cyclase activity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Elinogrel is the only selective, competitive, and reversible P2Y 12 inhibitor available in both IV and oral formulations. 8 It is a direct-acting P2Y 12 receptor inhibitor that does not require metabolic activation and thus has low potential for drug-drug interactions or genetic modulation.…”
Section: Editorial See P 328mentioning
confidence: 99%
“…8 It is a direct-acting P2Y 12 receptor inhibitor that does not require metabolic activation and thus has low potential for drug-drug interactions or genetic modulation. 8,9 Recently, the dose-ranging Intravenous and Oral Administration of Elinogrel to Evaluate Tolerability and Efficacy in Nonurgent PCI Patients (INNOVATE-PCI) phase 2b trial conducted in patients undergoing nonurgent PCI showed that elinogrel was not associated with increased major or minor bleeding, defined by Thrombolysis In Myocardial Infarction criteria, although there was an increase in bleeding requiring medical attention, primarily at the PCI access site.…”
Section: Editorial See P 328mentioning
confidence: 99%
See 2 more Smart Citations